2000
DOI: 10.1177/0310057x0002800107
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Orbital Morphine for Postoperative Analgesia in Pterygium Surgery

Abstract: A prospective double-blind study compared the analgesic effectiveness of peribulbar lignocaine with peribulbar morphine and lignocaine for postoperative analgesia in pterygium surgery. Twenty patients were randomly divided to receive a peribulbar injection preoperatively of either 1% lignocaine 2 ml or 1% lignocaine 1.6 ml and 4 mg morphine. Effects on pain at injection and pain at 24 hours and 48 hours postoperatively were measured with a visual analog pain scale. Effects of the injections on sedation, pupil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…There also have been attempts in local opioid analgesia for postoperative pain control after ophthalmosurgery. Pterygium patients receiving 4 mg of morphine plus 1.6 mL of lidocaine 1% (2-mL solution) injected peribulbar reported significantly lower pain scores 24 hours after pterygium surgery than the patients receiving injections of lidocaine 1% (2 mL) alone [49].…”
Section: Topical Wound Infiltrationmentioning
confidence: 93%
“…There also have been attempts in local opioid analgesia for postoperative pain control after ophthalmosurgery. Pterygium patients receiving 4 mg of morphine plus 1.6 mL of lidocaine 1% (2-mL solution) injected peribulbar reported significantly lower pain scores 24 hours after pterygium surgery than the patients receiving injections of lidocaine 1% (2 mL) alone [49].…”
Section: Topical Wound Infiltrationmentioning
confidence: 93%
“…Wishaw and coworkers compared different analgesic methods. 16 We found no references regarding postoperative pain and surgery time when comparing different methods in pterygium surgery. In this study we present a new method, where autologous conjunctival graft was glued on the sclera and we compare the results with those obtained with sutured grafts.…”
mentioning
confidence: 96%
“…There are many techniques and methods described for the management of postoperative pain. 5 Topical anesthetics may be administered to reduce postoperative pain. However, it was reported that they demonstrated serious 5 used morphine to prevent early postoperative pain after pterygium surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Topical anesthetics may be administered to reduce postoperative pain. However, it was reported that they demonstrated serious 5 used morphine to prevent early postoperative pain after pterygium surgery. It also was of a limited use after pterygium surgery as orbital morphine was applied by peribulbar injection that can cause serious complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation